Plasma Physics and Fusion Energy: A Promising Future for Sustainable Power Generation - Dahal, Suman (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2023)
The increasing global demand for electrical energy has led to a renewed interest in fusion research over the past couple of decades. As the world seeks environment-friendly and sustainable energy sources, fusion energy stands out as a potential solution to meet the ever-growing energy needs. Plasma physics and fusion energy research have gained significant momentum as potential solutions to address the ever-increasing global energy demand while mitigating environmental concerns. Fusion energy, mimicking the energy production mechanism of stars, holds immense promise as a safe, clean, and virtually limitless source of power. This research article provides an overview of plasma physics, explores the principles of fusion energy, and highlights the current advancements and challenges in this field. This research utilized a qualitative approach, incorporating a comprehensive literature review and data collection from scientific publications and databases. The findings were analyzed, synthesized, and interpreted, providing insights into the current state of plasma physics and fusion energy, including technological advancements, challenges, and future directions. It emphasizes the importance of continued research and development to unlock the full potential of fusion energy and pave the way toward a sustainable future.